The Influence of Self-Efficacy and Obedience Pressure on Audit Judgment with Task Complexity as a Moderating Variable - Dianty, Galuh Aura; Iskandar, Diah (Universitas Gorontalo, 2026)
This research aims to examine and obtain empirical evidence on the effect of self-efficacy and obedience pressure on audit judgment, with task complexity as a moderating variable. The population in this research consisted of all auditors working at Public Accounting Firms in the South Jakarta Region who were registered in the Directory of the Indonesian Institute of Public Accountants in 2024. The sample in this research comprised 108 auditors obtained using a non-probability sampling technique. Data were collected from May 9 to June 23, 2025, through the distribution of questionnaires. The analytical methods used to test the hypotheses in this research were multiple linear regression and moderation regression with the assistance of Statistical Package for the Social Sciences (SPSS) software version 25. The results indicate that self-efficacy has a positive and significant effect on audit judgment, while obedience pressure has no effect on audit judgment. In addition, task complexity does not moderate the influence of self-efficacy or obedience pressure on audit judgment.